BET proteins are associated with the induction of small airway fibrosis in COPD. Issue 7 (27th January 2021) - Zakarya, Razia; Chan, Yik L; Rutting, Sandra; Reddy, Karosham; Bozier, Jack; Woldhuis, Roy R; Xenaki, Dikaia; Van Ly, David; Chen, Hui; Brandsma, Corry-Anke; Adcock, Ian M; Oliver, Brian G
Abstract : Rationale: In COPD, small airway fibrosis occurs due to increased extracellular matrix (ECM) deposition in and around the airway smooth muscle (ASM) layer. Studies of immune cells and peripheral lung tissue have shown that epigenetic changes occur in COPD but it is unknown whether airway mesenchymal cells are reprogrammed. Objectives: Determine if COPD ASM cells have a unique epigenetic response to profibrotic cytokine transforming growth factor β1 (TGF-β1). Methods: Primary human ASM cells from COPD and non-COPD smoking patients were stimulated with TGF-β1. Gene array analysis performed to identify differences in ECM expression. Airway accumulation of collagen 15α1 and tenascin-C proteins was assessed. Aforementioned ASM cells were stimulated with TGF-β1 ± epigenetic inhibitors with qPCR quantification of COL15A1 and TNC . Global histone acetyltransferase (HAT) and histone deacetylase (HDAC) activity were assessed. chromatin immunoprecipitation (ChIP)-qPCR for histone H3 and H4 acetylation at COL15A1 and TNC promoters was carried out. Effects of bromoterminal and extraterminal domain (BET) inhibitor JQ1(+) on expression and acetylation of ECM target genes were assessed. Measurements and main results: COPD ASM show significantly higher COL15A1 and TNC expression in vitro and the same trend for higher levels of collagen 15α1 and tenascin-c deposited in COPD airways in vivo. Epigenetic screening indicated differential response to HDAC inhibition. ChIP-qPCR revealed histone H4 acetylation at COL15A1 and TNC promoters in COPD ASM only. ChIP-qPCR found JQ1(+) pretreatment significantly abrogated TGF-β1 induced histone H4 acetylation at COL15A1 and TNC . Conclusions: BET protein binding to acetylated histones is important in TGF-β1 induced expression of COL15A1 and TNC and maintenance of TGF-β1 induced histone H4 acetylation in cell progeny.